E0051 miR214 is upregulated during ventricular remodelling post MI. (17th November 2010) - Shi, Bing; Mi, Lin; Yu, Haiyi; Gao, Wei
Abstract : Objective: MicroRNAs (miRNAs) are endogeneous, single-stranded non-coding RNA molecules about 22 nucleotides long, del regulating target gene expression post-transcriptionally by base pairing with specific binding sites located in the 3' - untranslated regions (UTRs) of downstream target mRNAs. miRNAs play important roles in the regulation of a multitude of physiological functions such as cell differentiation, proliferation, apoptosis and immune response. Recent studies suggest that aberrant expression of miRNAs is associated with cardiovascular diseases. Those miRNAs exhibit unique spatial expression patterns that might become biomarker of diagnosis and target of treatment of ventricular remodelling. In present study, the expression level of miR-214 during ventricular remodelling post MI was detected. Methods: Rats underwent left descending coronary ligation or sham surgery. Rats with MI was assigned to two groups (n=5). Realtime PCR was developed to detect the expression of miR-214 in myocardium and plasma. Results: The expression level of miR-214 in both myocardium and plasma were up-regulated in the 14th and 28th day post MI. Compared to sham group, the expression level of miR-214 in myocardium increased by 33% (1.33±0.12 vs 1.00±0.02, p<0.01) in the 14th day and by 88% (1.88±0.08 vs 1.00±0.02, p<0.01) in the 28th day post MI. Compared to sham group, the expression of miR-214 in plasma increased by 60% (1.60±0.09 vs 1.00±0.06, p<0.01) in the 14th day and by 116% (2.16±0.13 vs 1.00±0.06, p<0.01) in the 28th day post MI. Conclusions: The expression level of miR-214 in myocardium and in plasma up-regulated in the progress of ventricular remodelling post MI in rat. The dynamic change of miR-214 may potentially become a new biomarker in ventricular remodelling post MI.